Effect of growing environment on graft compatibility and its success in cucurbits (Current Horticulture, 2024)
An experiment was conducted to evaluate the effect of growing environment on graft compatibility and its success in cucurbits,  at Kittur Rani Channamma College of Horticulture, Arabhavi, Belagavi district, Karnataka, during kharif 2018-19 and rabi  2019-20 seasons. Among both growing environments, (open field and shade net condition), field transplanted grafted plants  did not survive 20 days after grafting, hence the study was continued to know the performance of grafted plants under shade  net condition. Graft compatibility and its success was significantly influenced by different cucurbitaceous rootstocks and scions.  Significant and maximum graft success (89.33 and 96.33 %), maximum vine length (227.30 and 269.91cm 40 DAG), minimum  number of days to first and 50 % sprouting, final girth of graft union (16.36, 20.04, 13.37, 16.39 at 60 & 90 DAG), node number to  first female flower appearance (19.14, 8.28) and days to first female flower appearance (33.15, 45.62) were noticed in Momordica  charantia L. and Luffa acutangula L. scions grafted on Cucurbita moschata L. and Trichosathes cucumerina L. rootstocks during both  seasons and there was non-significant difference between two seasons.
Keywords: Cucurbits; Graft compatibility; Graft success; Growing environment; Wedge grafting method